(دافعية الإنجاز وعلاقتها بنتائج فِرَق المقدمة والمؤخرة بدوري كرة اليد) - المسالمة أحمد عبد الرحمن (Latakia University Journal -Medical Sciences Series, 2019)
تكمن أهمية البحث في الوقوف على حقيقة دافعية إنجاز النجاح وتجنب الفشل اللذين يشكلان دافعية الإنجاز؛ ودراسة علاقتهما بمستوى نتائج مراكز الفرق في دوري أندية الدرجة الأولى بكرة اليد في سورية. وخلص البحث إلى النتائج الآتية : هناك فروقات ذات دلالات إحصائية معنوية بين فرق المقدمة والمؤخرة؛ حيث ثبت أنّ دافع إنجاز النجاح يعبر عن المنافسة لتحقيق أفضل مستوى من الإنجاز لدى الرياضيين؛ وتعد مؤشراً على مستوى قبول التحدي والاستعداد للعطاء وبذل الجهد والاستجابة لما تتطلبه المنافسة والرغبة في الوصول لأفضل النتائج. كما تبين من الجدولين (٥) و(٦) وجود فروقات ذات دلالات معنوية في دافع تجنب الفشل لفرق المقدمة والمؤخرة، وأنَّ دافع إنجاز النجاح ودافع تجنب الفشل دافع مشترك في شخصية الفرد، ويمثل مطلباً غريزياً للاعب كي يتمكن من الحصول على درجة من الالتزام بين الشعور بالحاجة للإنجاز وتجنب الفشل في الوقت نفسه. Research Problem: The importance of the research is to learn the truth of success achieving motivation and failure avoiding which both form achieving motivation; in addition to studying their relation with the results of the first class teams of the Syrian national league. The research has concluded the following results : There are statistically significant differences between the top and rear teams, as it has been proven that the motivation of success achieving expresses the competition between the athletes to reach the best level of achievement. And it is considered a figure of the level of competition acceptance and making more efforts to respond to the competition needs and the desire of achieving better results. Table5 and table6 show that there are significant differences in the failure avoiding motivation of the top and rear teams, and both success achieving and failure avoiding motivations are a common motivation for one’s character, it also represents an instinctive need for the player to be able to reach a high degree of commitment according to both feelings; need for achievement and failure avoiding at the same time.